2022
DOI: 10.3390/foods11203197
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Effects of Calcium Lactate on the Gelling Properties of Large Yellow Croaker (Pseudosciaena crocea) Surimi by Low-Field Nuclear Magnetic Resonance and Raman Spectroscopy

Abstract: Divalent calcium ions (Ca2+) are often used in surimi gels to improve their physicochemical characteristics. The present study aimed to investigate the effect of calcium lactate on the physicochemical properties, state distribution of water, and protein structure changes of surimi gels made from large yellow croaker. The results showed that the addition of calcium lactate (0%, 0.5%, 1.5%, 2.5%, 3.5%, and 4.5% on wet surimi) significantly (p < 0.05) increased gel strength and whiteness, while cooking loss de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…PBC and STPP are alkaline, which has an influence on the protein structure and breaks the bonds between proteins [ 37 ]. Due to the pH and ion strength of cooked silver carp batters with PBC being higher than the sample with STPP, when using PBC to replace STPP, the α-helix structure unfolds, gradually transforming into β-sheet and β-turns structures [ 38 , 39 ]. Moreover, the α-helice and random coil structures content have a tendency to decrease, accompanied by β-sheet and β-turns structures content which have a tendency to increase, while the T2 and T3; T3, T4, and T5 samples were not significantly different ( p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…PBC and STPP are alkaline, which has an influence on the protein structure and breaks the bonds between proteins [ 37 ]. Due to the pH and ion strength of cooked silver carp batters with PBC being higher than the sample with STPP, when using PBC to replace STPP, the α-helix structure unfolds, gradually transforming into β-sheet and β-turns structures [ 38 , 39 ]. Moreover, the α-helice and random coil structures content have a tendency to decrease, accompanied by β-sheet and β-turns structures content which have a tendency to increase, while the T2 and T3; T3, T4, and T5 samples were not significantly different ( p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Adding functional ingredients such as starch, calcium ions, and transglutaminase can significantly improve the quality of surimi products. Sang et al [9] added different proportions (0 to 4.5%) of calcium lactate to large yellow croaker (Pseudosciaena crocea) surimi and found that calcium lactate could significantly improve its gelation properties, including its gel strength, whiteness, cooking loss and water holding capacity. The mechanism of calcium lactate enhancing surimi gelation was found to be related to the promotion of myosin stretching by divalent calcium ions and the formation of salt bridges between adjacent negatively charged proteins.…”
Section: Aquatic Product Processingmentioning
confidence: 99%
“…Calcium carbonate is a whitening agent commonly used as an additive in surimi [11]. Besides influencing the color, it turned out that calcium carbonate as a bleaching agent could enhance protein-protein interactions through the formation of salt bridges between myofibrils and divalent calcium ions [12].…”
Section: Introductionmentioning
confidence: 99%